2021
DOI: 10.3390/nu13124332
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Hypoglycemic Effects, Potential Mechanisms and LC-MS/MS Analysis of Dendropanax Trifidus Sap Extract

Abstract: Extracts of medicinal plants have been widely used to benefit human health. Dendropanax morbiferus (DM) has been well-studied for its anti-inflammatory and anti-oxidative effects, while Dendropanax trifidus (DT) is a lesser-known ecotype phylogenetically similar to DM, which has received significantly less attention. Studies thus far have primarily focused on leaf and bark extracts of DM, and not much is yet known about the properties of either DM or DT sap. Therefore, here we performed in vivo toxicity and ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In our previous study, DT sap was compared with Acer Saccharum (AS) sap using liquid chromatograph-tandem mass spectrometer, and we observed that estradiol was abundantly contained in DT sap compared to AS sap [ 25 ]. We were interested in knowing if estrogen may be an active component in DT sap-mediated signaling, thus we utilized human ERα-HeLa-9903 cell lines which contain a luciferase reporter gene at downstream of an estrogen responsive promoter element.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous study, DT sap was compared with Acer Saccharum (AS) sap using liquid chromatograph-tandem mass spectrometer, and we observed that estradiol was abundantly contained in DT sap compared to AS sap [ 25 ]. We were interested in knowing if estrogen may be an active component in DT sap-mediated signaling, thus we utilized human ERα-HeLa-9903 cell lines which contain a luciferase reporter gene at downstream of an estrogen responsive promoter element.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous report, we identified estrogen as one of the major components of DT sap [ 25 ]. In this study, we found that DT sap can signal through estrogen receptor alpha ( Figure 4 A).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations